TRI HITA KARANA SEBAGAI IDEOLOGI KEHIDUPAN MASYARAKAT BALI DALAM PENGEMBANGAN DESA WISATA PENGLIPURAN BALI - Ni Putu Ika Candra Kirani; I Wayan Wahyu Kharisma; Ni Wayan Eka Purnami Asih; Ni Nyoman Intan Sawitri Saraswati; Ni Kadek Sri Ratihningsih; Ni Nyoman Ayu Suryandari (Universitas Triatma Mulya, 2022)
Tri Hita Karana is a Balinese philosophy of life that contains three elements that build a balance and harmonious relationship between humans and God (Parahyangan), fellow humans (Pawongan) and nature (Palemahan). Village tourism is part of a form of tourism, where a small group of tourists live in or near traditional life. Penglipuran Village is one of the tourist villages in Bali which is still thick with traditional life, customs and cultural preservation. The purpose of this study was to find out how the application of the teachings of Tri Hita Karana in the tourist village of Penglipuran and how the behavior of the people of Penglipuran Village in developing a tourist village with Tri Hita Karana as the ideology of Balinese life. The research method used is a qualitative research method using data collection methods of observation, interviews and documentation. The results of this study are that Penglipuran Village meets the criteria as a tourist village with the Tri Hita Karana ideology. Tri Hita Karana is used as an ideology in social life, but not only in the community but can be used as the development of the Penglipuran tourist village. The local community implements the Tri Hita Karana ideology in carrying out their daily lives which makes Penglipuran Village prosperous with the three elements of Tri Hita Karana that work together to achieve harmony in life. The implementation of Tri Hita Karana in Penglipuran Village which is still maintained until now has an impact on the development of the Penglipuran Tourism Village with various traditions/customs as well as the wealth and natural beauty that it has, making Penglipuran Village a Tri Hita Karana-based Tourism Village.